Friendship quality and empathy with the happiness of new students - Aulia, Nuraini Ria; Sholeh, Moh. (Universitas Ahmad Dahlan, 2024)
High levels of happiness have a positive impact on students' academic continuity. This study aims to examine the relationship between friendship quality and empathy with the happiness of new students. The method used in this study is quantitative correlational, with a sample size of 368 new students. The sampling technique used is probability sampling. Three measurement tools were used: the Happiness According Scale, the Friendship Quality Scale (FQUA), and the Interpersonal Reactivity Index (IRI). Data analysis was performed using multiple linear regression. The results of the study show that there is a significant relationship between friendship quality and empathy with happiness. Individuals with good friendship quality and high empathy will experience increased happiness. Partial tests also illustrate the influence of each variable, with both friendship quality and empathy contributing to individual happiness. The conclusion of this study is that there is a significant relationship between friendship quality and empathy with the happiness of new students at Sunan Ampel State Islamic University Surabaya.